2003
DOI: 10.1095/biolreprod.102.011684
|View full text |Cite
|
Sign up to set email alerts
|

Decidual Activin: Its Role In the Apoptotic Process and Its Regulation by Prolactin1

Abstract: Successful pregnancy requires profound differentiation and reorganization of the uterine tissues including, as pregnancy progresses, extensive apoptosis of decidual tissue to accommodate the developing conceptus. We have previously shown a positive correlation between expression of activin A and apoptosis in the decidua and have also shown that expression of activin A occurs at the time when prolactin (PRL) receptors disappear from decidual cells. The goals of this study were to examine whether activin A plays… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 41 publications
0
17
0
Order By: Relevance
“…The neurotrophic function of activin A after hypoxic-ischemic brain injury (11,(22)(23)(24)(25) enhances the survival of midbrain and hippocampal neurons (24,25 ), decreases ischemic brain injury in infant rats (11 ), and shields striatal and midbrain neurons against neurotoxic damage (22,23,25 ). These findings and the evidence that activin A prevents apoptosis (26 ) and inhibits caspase (27 ), 2 important pathways involved in neuronal death (28 ), support the hypothesis that oversecretion of activin A in the presence of hypoxia/asphyxia may serve a neuroprotective function, reducing neuronal Clinical Chemistry 52, No. 8,2006 loss from brain injury.…”
Section: Discussionmentioning
confidence: 95%
“…The neurotrophic function of activin A after hypoxic-ischemic brain injury (11,(22)(23)(24)(25) enhances the survival of midbrain and hippocampal neurons (24,25 ), decreases ischemic brain injury in infant rats (11 ), and shields striatal and midbrain neurons against neurotoxic damage (22,23,25 ). These findings and the evidence that activin A prevents apoptosis (26 ) and inhibits caspase (27 ), 2 important pathways involved in neuronal death (28 ), support the hypothesis that oversecretion of activin A in the presence of hypoxia/asphyxia may serve a neuroprotective function, reducing neuronal Clinical Chemistry 52, No. 8,2006 loss from brain injury.…”
Section: Discussionmentioning
confidence: 95%
“…Studies of activin expression patterns during decidualization in mice and rats have further suggested that activin expression may regulate decidual regression during placentation (22,63,64), and activin signaling is thought to regulate interactions between the fetal placenta and maternal decidua in humans (65,66); however, the roles of activin signaling in the decidua have not been well studied experimentally in vivo.…”
Section: (A) Expression Ofmentioning
confidence: 99%
“…Although the substrates for HtrA1 are yet to be identified, a recent study indicated that HtrA1 might be involved in regulating the TGF␤ signaling (Oka et al, 2004). Given that TGF␤ family members have been implicated in regulation of decidual regression during placental development (Moulton, 1994;Tessier et al, 2003), it is tempting to suggest that HtrA1 may exert its action in decidual involution in association with the TGF␤ signalling.…”
Section: Localization Of Htra1 Protein In the Uterus And Placentamentioning
confidence: 99%
“…Members of the transforming growth factor (TGF) ␤ family, including TGF␤1, TGF␤2 and activin have been implicated in regulation of decidual regression during placental development (Moulton, 1994;Tessier et al, 2003). In addition, apoptosis-associated factors, including sulfated glycoprotein-2, the caspase family proteases such as cathepsin-D, Bax, and Bcl2 have been shown to be associated with decidual regression (Gu et al, 1994;Moulton, 1994;Dai et al, 2000).…”
Section: Introductionmentioning
confidence: 99%